2019
DOI: 10.1097/cad.0000000000000694
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical testing of 5-amino-1-((1R,2S,3S,4R)-2,3-dihydroxy-4-methylcyclopentyl)-1H-imidazole-4-carboxamide

Abstract: Protein kinase C-iota (PKC-ι) is an oncogene overexpressed in many cancer cells including prostate, breast, ovarian, melanoma, and glioma. Previous in-vitro studies have shown that 5-amino-1-((1R,2S,3S,4R)-2,3-dihydroxy-4-methylcyclopentyl)-1H-imidazole-4-carboxamide (ICA-1s), a PKC-ι specific inhibitor, is effective against some cancer cell lines by decreasing cell growth and inducing apoptosis. To assess ICA-1s as a possible therapeutic, in-vivo studies using a murine model were performed. ICA-1s was tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…Thus, in insulin-resistant, hyperinsulinemic states, these agents can reduce brain aPKC activity (i) at lower doses, indirectly via inhibition of liver aPKC and reduction of blood insulin levels, and (ii) at higher doses, by directly inhibiting brain aPKC. In this regard, note that, in published (38) and other pharmacokinetic/pharmacodynamic (PK/PD) studies, it was found that ICAP preferentially distributes to liver, but clearly passes the BBB to enter the brain. And, as found in other studies, ICAP is effective in liver and brain when given insufficiently increased doses by oral gavage (i.e., per os [PO]), as well when administered IV or SC.…”
Section: Apkc Inhibitorsmentioning
confidence: 97%
“…Thus, in insulin-resistant, hyperinsulinemic states, these agents can reduce brain aPKC activity (i) at lower doses, indirectly via inhibition of liver aPKC and reduction of blood insulin levels, and (ii) at higher doses, by directly inhibiting brain aPKC. In this regard, note that, in published (38) and other pharmacokinetic/pharmacodynamic (PK/PD) studies, it was found that ICAP preferentially distributes to liver, but clearly passes the BBB to enter the brain. And, as found in other studies, ICAP is effective in liver and brain when given insufficiently increased doses by oral gavage (i.e., per os [PO]), as well when administered IV or SC.…”
Section: Apkc Inhibitorsmentioning
confidence: 97%
“…PKCζ expression is positively correlated with poor overall survival in prostate cancer [ 289 ]. Inhibitors of PKCζ and λ/ι are therapeutic molecules for prostate cancer [ 290 , 291 , 292 , 293 ]. For example, treatment with the aPKC inhibitors 2-acetyl-1,3-cyclopentanedione (ACPD) and ICA-1 significantly decreased malignant cell proliferation and induced apoptosis [ 290 , 291 ].…”
Section: Pkc Isozymes As Prognostic Biomarkers or Therapeutic Targets...mentioning
confidence: 99%
“…Inhibitors of PKCζ and λ/ι are therapeutic molecules for prostate cancer [ 290 , 291 , 292 , 293 ]. For example, treatment with the aPKC inhibitors 2-acetyl-1,3-cyclopentanedione (ACPD) and ICA-1 significantly decreased malignant cell proliferation and induced apoptosis [ 290 , 291 ]. Furthermore, inhibition of aPKCs attenuates prostate cancer cell metastasis by downregulating vimentin expression [ 293 ].…”
Section: Pkc Isozymes As Prognostic Biomarkers or Therapeutic Targets...mentioning
confidence: 99%
“…The same group also characterized a PRKCI selective inhibitor 5-amino-1-(1R,2S,3S,4R)-2,3-dihydro xy-4-methylcyclopentyl)-1H-imidazole-4-carboxamide [67,68]. This compound has been tested in murine models [69]. Importantly, this inhibitor does not inhibit PRKCZ at concentrations up to 5 μM [67].…”
Section: Apkc Inhibitorsmentioning
confidence: 99%